Chemoprevention of colorectal cancer with nonsteroidal anti-inflammatory drugs. - Hilmi, I.; Goh, K.L. (2006)
Colorectal carcinoma is one of the commonest solid organ tumors in the world and its prevalence appears to be increasing in Asia. Recently, there has been much interest in various chemotherapeutic agents for the management of this condition, in particular nonsteroidal anti-inflammatory drugs (NSAIDs). There is a large amount of data that suggest traditional NSAIDs, as well as the new cyclooxygenase (COX)-2 selective inhibitors such as rofecoxib and celecoxib, have a role in the setting of primary and secondary prevention, and adjuvant therapy of both sporadic colorectal carcinoma and familial adenomatous polyposis. This review examines some of this data, as well as the potential problems and limitations of using these agents, particularly in light of the recent withdrawal of rofecoxib.